Distribution and abundance of walleye pollock Theragra chalcogramma in the northwestern Bering Sea in the summer-fall period of 2020 and their interannual variability - V. I. Polyanichko; M. Y. Kuznetsov (Известия ТИНРО)
Spatial distribution and abundance of walleye pollock are considered for the northwestern Bering Sea in the summer-fall of 2020 on the data of echo-integration trawl-acoustic survey. The pollock aggregated mostly in the shelf areas with positive or close to zero water temperature, with the higher concentration in the high-gradient zones. The densest aggregations (> 300 . 103  pcs./nmi2) were found in the eastern part of the Gulf of Anadyr and at the line between the economic zones of Russia and USA. Characteristic acoustic images and daily distribution of walleye pollock on the survey transects are presented. Spatial and bathymetric differentiation of certain size groups of pollock are revealed. More than 83 % of the fish were counted in the areas with bottom depth of 50–150 m. Immature walleye pollock with the size of 21–37 cm accumulated mainly in the areas with bottom depth of 75–125 m. Interannual dynamics of the size composition and abundance of walleye pollock in the northwestern Bering Sea is considered on the data of trawl-acoustic surveys in 2013–2020. The fluctuations of abundance and distribution are compared with changes of thermal conditions. Significant dependence of the pollock abundance on the mean anomaly of bottom temperature is confirmed (correlation coefficient +0.69): the species biomass was noticeably higher and its distribution was wider in the years with favorable (relatively warm) thermal regime than in cold periods.